Parenteral and Early Enteral Feeding in Patients with Colonic Tumor - O. A. Malkov; V. T. Dolgikh; A. O. Girsh (Общая реаниматология, 2008)
Objective: to provide evidence whether it is expedient to use an early enteral feeding protocol in patients with colonic malignancies in the postoperative period to prevent and to correct hemodynamic disorders, oxygen imbalance, and malnutrition. Subjects and methods. A hundred patients (61 males and 39 females) aged 66.2±5.0 years, who had Stages 2—3 colonic malignancies, were examined. Two algorithms of postoperative management were analyzed using the traditional diet and early enteral feeding. Results. The early enteral feeding protocol improves central hemodynamics and oxygen and nutritional status, prevents moderate protein-energy deficiency in the early postoperative period and reduces the number of complications and fatal outcomes in patients with colonic malignancies. Key words: malignancies, malnutrition, hemo-dynamics, oxygen status, enteral feeding.